Komunikasi Pemasaran Pakaian Adat Bali Melalui Facebook - Budawati, Ni Putu Sudewi; Febriyani, Ida Ayu Indah (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2025)
Abstract The development of information technology has changed conventional sales to online sales. Social media is widely used as a product marketing medium. The existence of online marketing can help in promoting and marketing the products offered to all people. Similar to the marketing carried out by Balinese traditional clothing traders, Facebook is used to market their products. This study aims to produce an effective form of marketing communication for traditional Balinese clothing through Facebook in the city of Mataram, identify and analyze the inhibiting factors of using Facebook in marketing communications for Balinese traditional clothing in the city of Mataram and find and analyze solutions to the obstacles to using Facebook in marketing communications for Balinese traditional clothing in the city of Mataram. This study used a qualitative method while the data were obtained from observation, interviews and documentation. The results showed that the effective form of marketing communication for traditional Balinese clothing through Facebook in the city of Mataram were advertising, sales promotion, public relations & publicity and personal selling. Inhibiting factors faced are physical barriers, sematic barriers, obstacles can also come from internal barriers, process barriers that originate from message senders. The solution to overcome the barriers to using Facebook in marketing communications for traditional Balinese clothing in the city of Mataram is to provide all the facilities needed in online marketing, for example the existence of wifi or the use of pedana cards that have a strong internet network, use the right language, create other accounts, consumers visit directly location of a traditional Balinese clothing shop, use of the right language, directly visiting the shop location, training namely photography training. Keywords: marketing communication, Balinese traditional clothing, facebook.